Non-invasive skin sampling detects systemically administered drugs in humans - Panitchpakdi, Morgan; Weldon, Kelly C.; Jarmusch, Alan K.; Gentry, Emily C.; Choi, Arianna; Sepulveda, Yadira; Aguirre, Shaden; Sun, Kunyang; Momper, Jeremiah D.; Dorrestein, Pieter C.; Tsunoda, Shirley M. (PloS one, 2022)
Clinical testing typically relies on invasive blood draws and biopsies. Alternative methods of sample collection are continually being developed to improve patient experience; swabbing the skin is one of the least invasive sampling methods possible. To show that skin swabs in combination with untargeted mass spectrometry (metabolomics) can be used for non-invasive monitoring of an oral drug, we report the kinetics and metabolism of diphenhydramine in healthy volunteers (n = 10) over the course of 24 hours in blood and three regions of the skin. Diphenhydramine and its metabolites were observed on the skin after peak plasma levels, varying by compound and skin location, and is an illustrative example of how systemically administered molecules can be detected on the skin surface. The observation of diphenhydramine directly from the skin supports the hypothesis that both parent drug and metabolites can be qualitatively measured from a simple non-invasive swab of the skin surface. The mechanism of the drug and metabolites pathway to the skin’s surface remains unknown.